Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Kaki Lima (Studi Kasus Wisata Taman Jomblo Kotabaru Jambi Pasca Pandemi Covid-19) - Ratih Rosita; Irmanelly Irmanelly; Ermaini Ermaini (Universitas Batanghari Jambi, 2020)
The purpose of this study is to explain the factors that influence the income of street vendors (Case Study of Taman Jomblo, Kotabaru Jambi Tourism after the Covid-19 Pandemic) simultaneously and partially. This research method is a descriptive study with quantitative methods using multiple linear regression analysis tools. The research sample was 58 from a total population of 136 traders. Data collection was carried out using a questionnaire. The results of the study are based on the results of multiple linear regression, it is proven that simultaneously and partially the variables of packaging, capital and trading time have a significant effect on the income of street vendors (Case Study of Taman Jomblo Kotabaru Jambi Post-Covid-19 Pandemic). Based on the results of research recommendations that are expected to be input. The Jambi City government should pay more attention to these factors to increase the income of street vendors in order to improve the welfare of the community during the Covid-19 period like this, where there were many large layoffs. The number of business units that have the greatest influence on the number of workers, the more the number of small and medium enterprises that are established , the more jobs will be created, so that labor absorption will also increase and the unemployment rate can be suppressed.